ANALISIS PENGARUH CITRA MEREK, DESAIN PRODUK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU NIKE (Studi Kasus pada Konsumen Nike di Kota Semarang) - Farhan, Mohamad Yusuf; Kamal, Mustofa (Faculty of Economics and Business Diponegoro University, 2015)
Nowadays, the competition on sport shoes is getting more competitive. Each company design sport shoes with the best quality. The purpose of this research is to explain the effect of brand image, product design, and product quality influencing on purchasing decision of Nike’s sport shoes and also explain which variable has the biggest influence on the purchasing decision of Nike’s consumer.This research takes 100 respondents using Accidental Sampling technique as sample. The analysis used in this research is multiple linear regression analysis. There are three stages before conducting multiple linear regression analysis, validity and reliability testing and classical assumption testing. After all stages of multiple linear regression is done, the writer conducted goodness of fit test: individual parameter significance test (t test), simultant significance test (f test), and determination coefficient test (R2 test).The result of Regression analysis showed that the variable of brand image, product design, and product quality had positive influences to the purchasing decision with an equation Y = 0,276 X1 + 0,238 X2 + 0,405 X3. The most influential variable was product quality in the amount of 0,405, followed by brand image in the amount of 0,276, and the least influential variable was product design in the amount of 0,238. T test result showed that brand image, product design, and product quality individually had a significant influence on purchase decision. This equation model had F value of 29,546 with a significant level of 0.0000. The analysis used determination coefficient or R2 test showed that 46.4% purchasing decision could be summarized by brand image, product design, and product quality and 53.6% purchasing decision could be summarized by other variables which had been explained by another factor.